The Implementation of Learning the Book of Al-Ghayah Wa At-Taqrib in Increasing Understanding of Thaharah in Class II Madrasah Isti'dadiyah Darul Falah - Shihab, Elza Fauziyah; Q, Ikhwan Aziz; Wijaya, Adi (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Book learning Al-Ghayah wa At-Taqrib has an important role in increasing students' understanding of concepts thaharah in Islamic jurisprudence, especially in the Shafi'i school of thought. However, in its implementation there are several obstacles, such as the lack of active involvement of students in learning and limited time available to study the material in depth. Apart from that, previous learning methods were still passive, causing students' understanding of thaharah less than optimal, especially in distinguishing between types of uncleanliness and the correct procedures for cleansing. This research aims to analyze the effectiveness of the book's learning method in deepening students' understanding of thaharah. Using a qualitative approach with descriptive methods, this research was conducted in an Islamic boarding school environment that applies the book Al-Ghayah wa At-Taqrib as the main teaching material in fiqh. Data was collected through observation, interviews and documentation, then analyzed in depth. The research results show that the lecture, discussion and direct practice methods applied in learning this book are able to increase students' understanding of concepts thaharah significantly. Thus, this research confirms that book learning Al-Ghayah wa At-Taqrib can be an effective strategy in deepening the understanding of thaharah fiqh for students.